Opening the Leontief's black box - Mustafin, A. (Heliyon, 2018)
The paper attempts to reconstruct what goes on inside the black box of the fixed proportions production function underlying the matrix of technical coefficients in the famous Leontief's input–output analysis. The approach is based on an idea that the conversion of inputs to outputs in industrial supply chains occurs in much the same manner as does the conversion of substrates into different molecules in enzyme-catalyzed biochemical reactions. A bottleneck principle is derived according to which at any moment the steady-state output of a multi-resource, one-product supply chain is completely controlled by a sole, most deficient, factor of production. This dramatic shrinkage of complexity is made possible owing to two key features of the input–output production units comprising the chain: saturated response of the output to the inventory level and weak buffer inventory leakage.